AfCFTA: Does it fast-track structural transformation in Senegal? - Maty Sall, Leysa (2021)
The African Continental Free Trade Agreement (AfCFTA) has recently entered into force and it appears as a possibility of economic growth and structural transformation for most African countries. Senegal is among the 54 countries that had signed and the 28 countries that had ratified the agreements.The aim of this paper is to evaluate the impact of intra-Africa tariff reduction/elimination in the AfCFTA framework for Senegal industrial transformation through trade and labour market impact. Four scenarios of the AfCFTA have been simulated, from full to partial liberalization, with a Senegal multi-sector static CGE model based on the STAGE CGE model. The economic transformation is assessed in terms of both international trade composition (intra-African versus trade with the rest of the world), domestic output, consumption pattern in rural and urban regions of the country and main macroeconomic indicators. Results suggest some trade diversion effects. Assuming the elimination of Senegal tariffs on all African products, main increase on imports come from sectors such as forestry, tobacco, grain milling, leather and footwear, and food crops. In addition, production increases mainly for manufacturing sectors including manufactured food , chemicals, cash crops , processed tobacco, hotels, fertilizers and machines . In contrast, production decreases for mining products, glass and pottery , food crops and forestry whose production is substituted by imports. Members can experience changes in production and consumption structures, by improving value chains integration through trade. Finally, macroeconomic impacts show that the elimination of trade barriers has the potential to boost trade and transform the production structure of Senegalese economy. However, the choice of sensitive products to be excluded is critical and have several implications.